Effect of External Resistance on the Efficiency ofthe Thermal Cell - H. Hussein, Falah; M. Sarhan, Waleed; N. Alkhateeb, Ahmed; D. Omran, Kareem (Asian Journal of Chemistry, 2010)
The effect of resistance on voltage with time for the laboratory thermal cell has been carried out by loading resistances of the range 1–1800 ohm. The 1800 ohm resistance proved to be the best because of exhibiting a steady discharge beside the longest period for consumption of the cell which approached 65 sec. The passing current across the resistance was of 0.44 mA, whereas the voltage for the closed circuit was 0.62 V, which was the highest value with the lowest current, compared with the other resistances. Investigation of the same effect of the same range of resistances, i.e., 1–1800 ohm was accomplished with the assembled cell. The results showed that the 1800-ohm resistance was again the best because it gave rise to a steady discharge accompanied with the longest period, which was close to 110 s. The passing current through the resistance was of 1.2 mA, while the voltage for the closed circuit was 1.94 V, which was the highest value with the lowest current, compared with other resistances.